Carbon-supported MnO2 nanoflowers: Introducing oxygen vacancies for optimized volcano-type electrocatalytic activities towards H2O2 generation. (1st April 2018) - Aveiro, Luci R.; da Silva, Anderson G.M.; Antonin, Vanessa S.; Candido, Eduardo G.; Parreira, Luanna S.; Geonmonond, Rafael S.; de Freitas, Isabel C.; Lanza, Marcos R.V.; Camargo, Pedro H.C.; Santos, Mauro C.
Abstract: Manganese oxide (MnO2 ) nanomaterials represent a promising low-cost electrocatalyst material for hydrogen peroxide (H2 O2 ) production by the oxygen reduction reaction (ORR). In this material, the introduction of oxygen vacancies is an effective strategy for boosting their electrocatalytic activities. Although the importance of oxygen defects in MnO2 -based catalysts has been shown in some electrochemical systems, a facile strategy for controlling the number oxygen vacancies in MnO2 -based catalysts and the systematic investigation of the effect of the vacancies on their electrocatalytic activities towards the ORR and H2 O2 electrogeneration remains limited. Here, we describe the synthesis of hybrid materials composed of MnO2 nanoflowers supported on Vulcan XC-72 carbon in which the concentration of the surface oxygen vacancy sites was increased. Surprisingly, we found a volcano-type relationship between the activity and the MnO2 loading. RRDE experiments showed the greatest formation of hydroperoxide ion in alkaline media for MnO2 /C 3% on carbon, displaying the highest electrocatalytic activity. This result was maintained for hydrogen peroxide during the electrolytic process using gas diffusion electrodes in acidic media. We suggest that the optimized catalytic activities observed for the MnO2 /C 3% catalyst are a result of (i) the high concentrations of oxygen vacancies at the catalyst surface, which promote the generation of highly catalytically active sites towards the ORR; (ii) their strong metal oxide-carbon interactions with modification of the carbon surface; (iii) the high surface area observed for the MnO2 nanoflowers supported on Vulcan XC-72; and (iv) the use of a MnO2 nanostructure displaying well-defined shapes and uniform sizes (with petals measuring 10 ± 5 nm in width) displaying a uniform dispersion over the carbon support. We believe the results described herein shed new light on the understanding of the role of the oxygen vacancies in the electrogeneration of H2 O2, which has important implications for the design of MnO2 -based electrocatalysts.